2010
DOI: 10.1161/hypertensionaha.109.142505
|View full text |Cite
|
Sign up to set email alerts
|

Neointimal Hyperplasia and Vasoreactivity Are Controlled by Genetic Elements on Rat Chromosome 3

Abstract: Neointimal Hyperplasia (NIH) can lead to restenosis after clinical vascular interventions. NIH results from complex, and poorly understood, interactions between signaling cascades in the extracellular matrix and disrupted endothelium which leads to vessel occlusion. Quantitative Trait Loci (QTLs) were previously reported on rat chromosomes 3 and 6 through linkage analysis of post-injury NIH in mid-iliac arterial sections. In the current study, substitution mapping validated the RNO3 NIH QTL but not the RNO6 NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This overlaps with loci identified for BP in the DS [25], Fawn-Hooded hypertensive (FHH) [26] and SHR rats [27]. However, this locus is distinct from two additional BP QTLs previously identified and confirmed in DS rats [28,29].…”
Section: Discussionsupporting
confidence: 49%
“…This overlaps with loci identified for BP in the DS [25], Fawn-Hooded hypertensive (FHH) [26] and SHR rats [27]. However, this locus is distinct from two additional BP QTLs previously identified and confirmed in DS rats [28,29].…”
Section: Discussionsupporting
confidence: 49%
“…Sprague-Dawley and Wistar rats are frequently used strains for atherosclerosis and neointimal hyperplasia research. Rats that mimic certain aspects of cardiovascular pathophysiology, such as the spontaneously hypertensive rat ( 71 ) or the obese rat versus the lean Zucker rat [diabetes type 2 ( 72 )], can be used to study the specific influence of key cardiovascular risk factors on neointimal hyperplasia. These models, combined with angioplasty procedures (eg, stenting), allow for a more translational investigation of cellular and molecular processes of restenosis compared with mere dietary or mechanical injury models ( 73 ).…”
Section: Rat Models Of Neointimal Hyperplasiamentioning
confidence: 99%
“…Studies from our laboratory have demonstrated that heritable genetic variations encode physiological differences in vascular reactivity within the arterial wall ( 10 ). Specifically, we found increased vasoconstriction in SHR vessels compared with Brown Norway (BN) vessels in response to serotonin and prostaglandin F2α, and when the rat chromosome 3 (RNO3) alleles from the BN rat are introgressed to form the SHR.BN3 congenic strain, there is a further increase in vasoconstriction when compared with that observed in the parental SHR vessels ( 11 ). Given that increased vasoconstriction may lead to increased blood pressure, we sought to determine if the congenic SHR.BN3 strain demonstrates increased blood pressure compared with the parental SHR strain, and to further compare and characterize the relative stiffness, arterial wall structural components and extracellular matrix (ECM) of the SHR.BN3 and SHR strains using ultrasound and multiphoton microscopy (MPM).…”
Section: Introductionmentioning
confidence: 84%